Homosexuality in Contemporary Islamic Legal Approaches: Study of Huzaemah Tahido Yanggo’s Thought - Amri Amri; Athoillah Islamy (Al-'Adl, 2022)
This study intends to identify the epsitemology of Islamic law of Huzaimah Tahido Yanggo with the contemporary maqasid sharia approach formulated by Jasser Auda. This literature research uses a normative-philosophical approach.The main research data is Huzaemah Tahido Yanggo's scientific work entitled Sexual Deviance (LGBT) in the View of Islamic Law (2018). Secondary data in the form of books, journals, theses and dissertations that are relevant. The nature of this research approach is descriptive-analytic. Data analysis techniques include data reduction, data presentation, and data verification. The results showed that Huzaemah Tahido Yanggo's Islamic legal epistemology of homosexual behavior is a multidimesional approach to Islamic law, and has a preemptive-socialist orientation. Such a big conclusion is based on the epistemological foundation of Islamic law Huzaemah, as follows First, the foundation of the epsitemology of islamic law is comprehensive, not partial in accordance with the character of the features of the comprehensive Islamic legal approach. So, there is no tendency towards a dichotomous and partial approach to Islamic law. Second, the epistemological foundation of Islamic law that emphasizes meaning, which is to have a relationship with various Islamic legal orientations towards the monasticism of homosexual behavior, such as the value of maqasid in the form of the benefit of the soul (hifz al-nafs), and also the misfortune of regeneration of offspring (hifz al-nasl), even the expansion of the broader dimension of benefit, namely hifz waton (maintaining the safety of the state).The theoretical implication of this research shows that the paradigm of contemporary Islamic law that prohibits homosexual behavior is not based on a pragmatism and individualist approach to Islamic law, but a multidimensional approach to Islamic law, and has a preventive-socialist orientation.There are limitations to the study, namely that it has not identified the method of interpretation that Huzaemah used to the theological basis of homosexual law.